Evaluasi Strategi Pemasaran Produk Bakery and Pastry di Lobby Lounge Hotel Fairfield By Marriott Surabaya - Farah Hanan Asma’ Annisa; Niken Purwidiani; Asrul Bahar; Ita Fatkhur Romadhoni (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the implementation and evaluation results of the marketing strategy for bakery and pastry products sold in the lobby lounge of Hotel Fairfield By Marriott Surabaya. This study used a combined qualitative and quantitative approach to obtain a more comprehensive picture. Data collection techniques were conducted through direct observation at the research location and interviews with relevant parties. Furthermore, data analysis was also strengthened by distributing a Likert-based questionnaire to three main respondents: the F&B Manager, the Daily Worker Pastry, and the Marketing Team. This mixed-method approach allowed the researcher to capture both numerical evaluation and in-depth qualitative insights. The results showed that the product strategy has been running quite well, especially in terms of quality and implemented work procedures. However, there are still weaknesses in the innovation aspect, as the products do not yet have distinctive characteristics that can serve as a key differentiator from competitors. In other words, the bakery and pastry products still lack a unique selling point that could strengthen brand identity. In terms of pricing strategy, the hotel uses a premium pricing system, which is considered appropriate for the image of a four-star hotel. However, this approach is still not flexible enough to optimally reach consumers outside the hotel. The promotional strategy is considered to have been implemented quite well, especially through bundling packages and the use of social media. However, existing promotions have not been implemented consistently and tend to be unstructured. Consistent promotion is essential to maintaining customer engagement and building long-term brand awareness. Meanwhile, the location strategy is considered quite effective because products are displayed in areas easily accessible to hotel guests. However, opportunities through digital distribution channels, such as online bookings, have not been maximized. Expanding digital distribution channels could significantly increase market reach and sales performance.